Determinación de colesterol sérico total en pacientes adultos de ambos sexos, atendidos en el puesto de salud de Buenos Aires Sur del distrito de Víctor Larco, en diciembre 2010” - Rodríguez Jiménez, Adrián David (2011)
In the present investigation we determined the serum cholesterol in adults of both sexes treated at the health post of Buenos Aires Sur District of Victor Larco, in December 2010 by enzymatic colorimetric methods according to Trinder, this will a sample of 54 adults, who were administered informed consent and a survey. Then we proceeded to sample collection and processing of the same, being read in a spectrophotometer at 505nm. With the data we obtained the following results: 55.55% of patients had normal cholesterol values, being 42.59% 12.96% women and men, 37.04% had high cholesterol limits, being 24.08% and 12.96% women men and 7.41% of patients had high cholesterol, by age and by gender. Therefore it is concluded that female patients ages 57 to 66 presents high limits and high cholesterol at a rate of 12.8% and 2.6% respectively in terms of male patients in the same range have the 13.34 % limits of high cholesterol, be the main cause increased intake of carbohydrates